(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purposes of this study are to (1) investigate the artistic style characteristics of modern Guangdong female calligraphers, (2) compare the similarities and differences of the Chinese females calligraphers, and (3) analyze the causes of their artistic characteristics from the perspectives of female calligraphers characteristics in modern Guangdong. This study adopts a qualitative design. Data were collected through books, museums, field trips and the Internet, and the data were relatively analyzed and studied. This study covers 12 Guangdong female calligraphers recorded in modern Chinese history.The research results showed that, on the surface, the painting and calligraphy art style of these female calligraphers belongs to the beautiful category, and when we carefully observe them, their inner spirit is different. Feng Wenfeng, Tan Rong, Zhang Kunyi and so on are mainly the beauty of masculinity, Xian Yuqing, Zheng indifferent, Wu Peirong and others are mainly the beauty of feminine. He Xiangning, Xiao Shufang, Kang Tongbi, Deng Mengxiang, Guan Zilan, Feng Zhonglian and so on are both rigid and soft. The personality charm of female calligraphers is the most important factor for their artistic style; the second background is the second factor for female calligraphers; the family support has a significant influence on their artistic style, and the influence on their artistic style. The results show that the modern female calligrapher successful primary factor is talent, free thought and independent.